Feasibility study of plasma electrolytic oxidation (PEO) on Tio2, nanotubes fabrication / Amirah Nadiah Roslan - Amirah Nadiah, Roslan (2018)
It is hard to find sufficient data on the formation of nanotube array in the surface of metal oxides by using plasma electrolytic oxidation process. One of the reason is because of the wide range of parameters and researchers are still doing research on this topic. In this research, the formation of TiO2 nanotubular arrays in the surface of Ti6Al4V substrate by using plasma electrolytic oxidation technique will be observed. Results obtained meet the objectives of the present study which is to obtain TiO2 nanotubes. The phenomenon of plasma discharge are as a result of dielectric breakdown that occurs when the applied voltage exceeds a certain threshold. The images of nanotubes are captured using FESEM and the analysis of elemental composition is done by EDX system. From the image obtained it can be concluded that only 43% of the substrate surface covered with nanotubular structure. The average diameter of the nanotubular structure is 95.6 nm and average tube wall thickness is 18.5 nm. The hardness for uncoated sample is 307.2 HV while average hardness for TiO2 nanotubes is 426.4 HV. This proved that PEO coating enhances the hardness of a substrate. The adhesive strength obtained is ~199 mN. The scratch line drawn by the diamond indenter is not smooth and showed rise and fall peaks in the penetration depth graph. This is because of high surface roughness or non-uniformly distributed coating throughout the substrate surface.